Advances in mergers and acquisitions. Vol. 4 - Cooper, Cary L.; Finkelstein, Sydney (Advances in mergers and acquisitions., 2004)
Advances in Mergers and Acquisitions brings together a series of articles on this topic from academics around the world with the expressed purpose of enhancing our knowledge of the entire M&A process, from strategic analysis to integration. It is the diversity of perspectives in particular that creates an opportunity to learn from others, each article representing an important piece of the overall puzzle, with the ultimate goal being to boost our understanding of the determinants, process, and consequences, of mergers and acquisitions.